SCRUTINIZING SEMANTIC STRUCTURE OF THE VERB “CHOOSE” - Ziyatov Akmal Tursunovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The problem of word-building is associated with prevailing morphological word-structures and with processes of making new words. Semantics is the study of meaning. Modern approaches to this problem are characterised by two different levels of study: syntagmatic and paradigmatic.